Effect of intra-articular inj-ction of radioactive colloids of erbium and yttrium on the growth of rabbit legs. - Rebut-Bonneton, C (1975)
The effect of the intra-articular injection of radioactive erbium 169 and yttrium 90 on the growth of the leg in rabbits has been studied. I colloid state these isotopes are used clinically for synovial ablation. These beta emitters slow down bone growth in proportion to the amount of radioactivity injected. If the joint has previously been damaged by an inflammatory arthritis the effect of the radiation on the bone growth is reduced.